Management of state projects and programs (Journal of Economic Research & Business Administration, 2016)
Nowadays development of economy of the Republic of Kazakhstan is realized through state programs and projects. Acceptance of ISO21500– «The Control of directive projects», as the national standard stimulates the state on a new step for more exact and profound studying of tools and methods of project management. The state programs are the largescale projects urged to solve problems with which only the state can manage. World experience of realization of state programs says that they can be re ally successful only when management will be carried out by the principles of design management. Taking into account rigid financial restrictions experience of professionals in the field of design management becomes more demanded than ever. Use of instruments of project management in devel opment and realization of state programs and projects will allow receiving unique result in due time and taking into account limitation of resources.
Keywords: state programs; program management; state program man agement; instruments of project management; Strategic development plan.